KUALITAS PAPAN PARTIKEL DARI LIMBAH BATANG KELAPA SAWIT DAN MAHONI DENGAN VARIASI PELAPIS BILAH BAMBU TALANG - Fradika Oktavianus Bernadi Siahaan; Rudi Hartono; Tito Sucipto (Peronema Forestry Science Journal, 2016)
Efforts to improve particle board quality was made from oil palm trunks waste and mahogany by coating the surface of the particle board using lath of talang bamboo. The purpose of this research to evaluate physical and mechanical properties of particle board that made from oil palm trunks and mahogany combination by lath of talang bamboo coating variation and to determined strength wood class from coating variation by lath of talang bamboo when optimal utilization. Treatment variations were without coating; face coating with the inside lath of bamboo, and face coating with the outside lath of bamboo; face and back coatings with inside and outside lath of bamboo. Thick coating from inside and outside lath of bamboo was 0.1-0.2 mm. Particle board size was 25 cm x 25 cm x 1 cm, density target was 0.7 gram/cm3, pressure was 30 kgf/cm2 and temperature was 170 oC for 10 minutes. The result of research will be compared with SNI 03-2105-2006 and PKKI-ni-5 in 1961. Statistic analysis used single completely randomized design with three repetitions. The result of these research showed that density value, moisture content, water absorption on 2 hours and 24 hours submersion, thickness swelling on 2 hours and 24 hours submersion, MOE value, MOR value, and IB value were 0.56-0.68 gram/cm3, 3.29-4.42%, 40.09-78.50% and 53.04-87.15%, 9.04-19.17% and 11.88-24.68%, 9,975.76-72,900.41 kg/cm2, 81.64-578.70 kg/cm2, and 0.91-2.59 kg/cm2, respectively. Coating variation by lath of talang bamboo were significantly affected on all of physical and mechanical particle board quality. The best treatment was on face and back coating variation that each used inside and outside lath of talang bamboo which had fulfilled all of the physical and mechanical SNI 03-2105-2006 and included into III of strength wood class according to PKKI-ni-5 in 1961.Key words: talang bamboo, oil palm trunks, mahogany, particle board, physical and mechanical properties